2010
DOI: 10.1523/jneurosci.5628-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Suppresses the Neuronal Cell Cycle by Disrupting the E2F1–DP1 Complex

Abstract: Neurons that reenter a cell cycle after maturation are at increased risk for death, yet the mechanisms by which a normal neuron suppresses the cycle remain mostly unknown. Our laboratory has shown that cyclin-dependent kinase 5 (Cdk5) is a potent cell cycle suppressor, and we report here on the molecular basis of this activity. Cell cycle suppression by Cdk5 requires its binding to the p35 activator protein. The related p39 and p25 proteins cannot serve as substitutes. Unexpectedly, Cdk5 enzymatic activity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 48 publications
(50 reference statements)
1
99
0
Order By: Relevance
“…In the nucleus, CDK5 binds to the cell-cycle-associated transcription factor E2F1 to disrupt its association with its co-transcription factor DP1. This in turn attenuates E2F1 DNA interactions which consequently inhibits cell proliferation (28). Furthermore, we have shown that the antiproliferative function of CDK5 is mediated independently of its protein kinase activity (29)(30).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the nucleus, CDK5 binds to the cell-cycle-associated transcription factor E2F1 to disrupt its association with its co-transcription factor DP1. This in turn attenuates E2F1 DNA interactions which consequently inhibits cell proliferation (28). Furthermore, we have shown that the antiproliferative function of CDK5 is mediated independently of its protein kinase activity (29)(30).…”
Section: Discussionmentioning
confidence: 96%
“…The kinase activity of CDK5 has been thought to mediate carcinogensis of certain nongastric cancer types (39)(40)(41)(42)(43). Our previous studies indicated that nuclear CDK5 can function as a cell-cycle suppressor in the nervous system (28)(29)(30). In the nucleus, CDK5 binds to the cell-cycle-associated transcription factor E2F1 to disrupt its association with its co-transcription factor DP1.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Cdk5 exists in a 4-protein complex with p35, E2F1 and p27 (21,22), and we had previously shown that overexpression of p35 alone was capable of driving complex formation in N2a cells. We wondered, therefore, whether the formation of this complex would affect the ubiquitination of Cdk5 or other Cdks.…”
Section: Cdh1 Is the Ubiquitin E3 Ligase Thatmentioning
confidence: 99%
“…The p25 fragment, however, has been suggested to stabilize Cdk5 and result in its hyperactivation (24,31), suggesting that p25 might also be capable of inhibiting Cdk5 ubiquitination. The outcome of this experiment would also serve as a test of whether the larger E2F1/p27/p35 complex was involved since p25 is incapable of driving its formation (21). We used N2a cells to overexpress p25, p10, or ⌬P35, a mutant form of p35 that lacks the Cdk5 binding domain.…”
Section: Cdh1 Is the Ubiquitin E3 Ligase Thatmentioning
confidence: 99%
“…These results indicate that a certain amount of p35 and p39 can enter into the nucleus. Nuclear Cdk5 or nuclear free p35 is suggested to prevent re-entry of postmitotic neurons into cell cycle (Zhang et al, 2008;Zhang et al, 2010). On the other hand, it is well documented that dysregulation of Cdk5 activity by cleavage of p35 to p25 by calpain induces neuronal death (Patrick et al, 1999;Gong et al, 2003;Smith et al, 2006;Saito et al, 2007;Kim et al, 2008;Wen et al, 2008;Chang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%